Analyzing the operational conditions of crash carts in clinical and surgical hospitalization units - Vanessa Fortes da Silva; Daniele Delacanal Lazzari; Nara Reisdorfer; Simara Claudia Michaelsen; Adriana Eich Kuhnen (SciELO, 2021)
ABSTRACT Objective: To evaluate the operational conditions of crash carts in all clinical and surgical hospitalization units of public hospitals in a region in Southern Brazil. Method: Quantitative, cross-sectional study to evaluate crash carts in adult clinical and surgical hospitalization units. The data were collected through a checklist containing 16 continuous variables. Results: Nineteen crash carts in nineteen units were evaluated. Analysis shows that the most frequent problems were excess of equipment and its lack of organization, medication in incorrect compartments and/or with no identification, and inappropriate environment for transportation. Conclusion: The most relevant factors that possibly interfere with the operational conditions of crash carts are directly related to the organization and management of material resources, which may lead to the reduction of its functionality during patient care. Such problem may be solved by readjusting items and performing frequent verification.